Fecal microbiota transplantation treatment of autoimmune-mediated type 1 diabetes: A systematic review - Zhang, Shuo; Deng, Feiying; Chen, Jingxian; Chen, Fengwu; Wu, Zezhen; Li, Liping; Hou, Kaijian (Frontiers in Cellular and Infection Microbiology, 2022)
There is a strong link between fecal microbiota and the development of type 1 diabetes. As an emerging therapeutic modality, fecal microbiota transplantation has been shown to be safe and effective in the treatment of many intestinal and extraintestinal diseases. Various studies have found that fecal microbiota transplantation can treat diseases by correcting patients’ immune disorders. Besides, many studies have found that fecal microbiota transplantation can improve glycemic control and insulin resistance in diabetic patients. Therefore, this paper reviews the mechanism of action of fecal microbiota transplantation on autoimmune-mediated T1DM and the current research progress, feasibility, and issues that need to be addressed in the future development of fecal microbiota transplantation in the treatment of autoimmune-mediated T1DM.